Peningkatan Pengetahuan Siswa Smp Tentang Pentingnya Konsumsi Ikan Sebagai Sumber Gizi Melalui Kegiatan Penyuluhan Perikanan - Eti Natasya; Novia Ulya; Riki Hidayat; Nazri; Najwa Diah Kirana (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
The low level of fish consumption among school-aged children remains a serious nutritional problem in Indonesia, including in Sambas Regency. This condition has the potential to negatively affect the quality of children’s growth and development, considering that fish is a high-quality source of animal protein rich in omega-3 fatty acids, vitamins, and essential minerals that play an important role in supporting physical growth, brain development, and improving children’s learning concentration. A lack of knowledge and awareness regarding the benefits of fish consumption is one of the factors contributing to the low level of fish consumption among school-aged children. This community service activity aimed to increase the knowledge and awareness of junior high school students regarding the importance of fish consumption as asource of nutrition through fisheries extension activities. The activity was conducted at SMP Negeri 5 Sajad and involved 68 students from grades VIII and IX as participants. The methods used included interactive lectures, discussions, and the use of audio-visual media to facilitate understanding of the material. In addition, students’ knowledge levels were evaluated through pre-tests administered before the extension activity and post-tests conducted after the completion of the activity. The results showed a significant increase in students’ knowledge after participating in the fisheries extension activity. This was indicated by an increase in the average post-test scores compared to the pre-test scores, as well as an increase in the number of students categorized as having a high level of knowledge. Thisimprovement reflects that the extension methods used were able to attract students’ interest and were effective in conveying information related to the health and nutritional benefits of fish consumption. Therefore, this fisheries extension activity has proven to be effective as an effort to provide nutrition education from an early age and is expected to contribute to encouraging a sustainable increase in fish consumption among school-aged children.